Synthesis, Characterization, and Antifungal Evaluation of Some New 1,3,5-Trisubstituted Pyrazole Derivatives: Synthesis, Characterization, and Antifungal Evaluation of Some New 1,3,5-Trisubstituted Pyrazole Derivatives - Jain, Dr. Alok Pal (International Journal of Pharmaceutical & Biological Archive, 2020)
Objective: The objective of the paper was to design, synthesis, and characterization of new 1,3,5-trisubstituted-2-pyrazolines derivative and evaluate for antifungal activity. Materials and Methods: The 1,3,5-tri-substituted-2-pyrazolines derivatives have been synthesized by the reaction of chalcone derivatives with succinic hydrazide in the environment of pyridine. Total 20 compounds have been synthesized and characterized by the IR, 1H NMR, and mass spectral analysis. Antifungal activity of the compounds carried out on four fungal strains, that is, Saccharomyces cerevisiae, Aspergillus niger, Candida albicans, and Rhizopus oryzae in two different concentrations, that is, 50 and 100 Î¼g/ml by agar-diffusion method using cup-plate method and Ketoconazole was used as standard antifungal drug. Results and Discussion: In accordance with the data from antifungal activity, all the synthesized 1,3,5-trisubstituted pyrazole derivatives (ME1-ME8, CL1-CL8, and BR1-BR4) have shown mild to best activity against tested organisms. The data of antifungal activity against the fungal strains (S. cerevisiae, A. niger, C. albicans, and R. oryzae) suggested the order of activity of compounds: BR-3 > BR-2 > BR-1 > CL-4 > BR-4 > CL-3 > CL-2 > ME-3> ME-2 > CL-5 > CL-6 > ME-4 > ME-5 > ME-6 > ME-7 > CL-7 > CL-8 > ME-8 > CL-1 > ME-1. The presence of electronegative group (Br, Cl, F, and NO2) either at third and fifth position of 1,3,5-pyrazoline ring is required for the potent antifungal activity. The presence of electronegative group (Br, Cl) at third and fifth position may necessary for the best activity against bacterial and fungal strains but the addition of F, NO2 has shown the moderate activity but in case of -CH3 and -OCH3 substitution may diminish the activity. The series BR-1 to BR-4 is most active compound of the synthesized compounds. Conclusion: The 1,3,5-trisubstituted pyrazole derivatives has been successfully synthesized and antifungal activity of the compounds denotes that the series BR-1 to BR-4 is most active compound of the all twenty synthesized compounds. The addition of electronegative group (Br, Cl) at third and fifth position in pyrazole ring may necessary for the activity against fungal strains.